The Main Character Feelings in Anne Bradstreet Poems Collection - Aqidah, Vika Maslahatul; Sukmawaty, Fenty; Saprudin, Saprudin (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2023)
The title of this research is Perasaan Tokoh Utama dalam Kumpulan Puisi Karya Anne Bradstreet. This research aims to find ot the feelings of the main character and the deep structure in a poem collection by Anne Bradstreet. This research uses a descriptive qualitative method and objective approach. the result of the research show that the feelings experienced by the main character are due to the pain from illness she suffering from and the sadness she is experiencing. The main character also not only describe the feelings that she feel, but also there is a feeling of acceptance or surrender to all destiny that give by God, fear to the God and gratitude to the God. Keywords: Deep structure of the poem, Main character, Feeling